1933 Cal. Stat. 925 - (:unkn) unknown (My University, 1933)
Ch. 337, § 1: Required every person, firm, or corporation who knowingly posses or transports any form of shell, cartridge, or bomb containing or emitting tear gas is guilty of a public offense. Violators sentenced to state prison not exceeding two year or by fine not exceeding two thousand dollars, or both.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - NON-GUN ARMS